2006
DOI: 10.2337/dc06-1343
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex May Significantly Interact With Diabetes on the Risks of Lower-Extremity Amputation and Peripheral Revascularization Procedures

Abstract: OBJECTIVE -Using the National Health Insurance claim data, we prospectively investigated the age-and sex-specific incidence density and relative hazards of nontraumatic lowerextremity amputation (LEA) and peripheral revascularization procedure (PRP) of the diabetic population in Taiwan.RESEARCH DESIGN AND METHODS -A total of 500,868 diabetic patients and 500,248 age-and sex-matched control subjects, selected from the ambulatory care claim (1997) and the registry for beneficiaries, respectively, were linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 40 publications
2
66
0
1
Order By: Relevance
“…10 A previous study showed that the risk of nontraumatic lower extremity amputation due to diabetic complications was 9.22 and 11.67 times higher than that in the nondiabetic population for men and women, respectively. 11 Foot problems were present in 2.9% of the patients with diabetes, and ulcers represented 86.7% of all the initiating events. 12 Nevertheless, no nationwide epidemiologic survey of diabetic foot problems in Taiwan has been carried out and data on the treatment outcomes for diabetic foot ulcers are still not available.…”
Section: Introductionmentioning
confidence: 99%
“…10 A previous study showed that the risk of nontraumatic lower extremity amputation due to diabetic complications was 9.22 and 11.67 times higher than that in the nondiabetic population for men and women, respectively. 11 Foot problems were present in 2.9% of the patients with diabetes, and ulcers represented 86.7% of all the initiating events. 12 Nevertheless, no nationwide epidemiologic survey of diabetic foot problems in Taiwan has been carried out and data on the treatment outcomes for diabetic foot ulcers are still not available.…”
Section: Introductionmentioning
confidence: 99%
“…An individual was classified as being a diabetic patient if he or she had an initial diabetes-related diagnosis at any time in 2000 and was then diagnosed one or more times within the following 12 months. The first and last outpatient visits within 1 year were required to be >30 days apart to avoid accidental inclusion of miscoded patients [14]. To detect newly diagnosed AD, we excluded patients who sought treatment in hospitals or ambulatory care visits for AD (ICD-9 code 331.0) from 1997 to the first ambulatory care appearance in 2000 from our diabetic group.…”
Section: Methodsmentioning
confidence: 99%
“…26 To detect newly diagnosed malignant neoplasm cases, we excluded those patients admitted to the hospitals for any kinds of malignant neoplasm (ICD-9: 140-208) during 1997-1999 from our diabetic group. In Taiwan, BNHI issues major illness/injury certificates to all patients who suffer from malignant neoplasm, and these patients are exempt from copayment to the NHI if they are admitted for the illness associated with the related malignancy.…”
Section: Methodsmentioning
confidence: 99%